Investigation of calcium-phosphate in diet and digestibility of red tilapia - N. Eriyusni (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Investigation of calcium-phosphate and digestibility in Red tilapia was investigated. All diets were formulated at 0.5% calcium-phosphate in Diet1, 1.0% in Diet2 and 1.5% in Diet3, and was formulated to be isonitrogenous of 30% crude protein and energy: protein ration 30:2. The apparent digestibility coefficient of levels of calcium-phosphate were significant differences (P0.05) in faeces in upper and lower intestine. However digestibility of calcium and phosphorus in faeces in upper and lower intestine was higher in Diet2 with a value of 73.48 ± 0.33% and 70.54 ± 0.33%, 39.24 ± 0.02% and 43.73 ± 0.50%. Deposition of calcium and phosphorus was higher in Diet2 with a value of 9.03 ± 0.12% and 10.68 ± 0.24% in whole body, 10.17 ± 0.05% and 13.32 ± 0.41% in muscle, 13.06 ± 0.13% and 12.05 ± 0.01% in bone, 11.06 ± 0.47% and 10.01 ± 0.01% in scale and 6.01 ± 0.58% and 4.10 ± 0.58% in gill. The absorption gain of calcium and phosphorus were also higher in Diet2 with a value of 3.07 and 1.39% in whole body, 1.96 and 2.11% in muscle, 1.25 and 1.48% in bone, 0.97 and 0.89% in scale and 0.16 and 1.85% in gill. The overall digestibility was found to be higher in Diet2 with containing of 1.0% calcium phosphate and 30% crude protein compared to other diets.